Factors associated with self-medication among expatriate high school students: a cross-sectional survey in United Arab Emirates - Syed Ilyas Shehnaz; Jayadevan Sreedharan; Nelofer Khan; Khaled Jamal Issa; Mohamed Arifulla (Epidemiology, Biostatistics and Public Health)
The study aimed to assess factors associated with self-medication (SM) among expatriate high school students of United Arab Emirates using a validated questionnaire. Most common reasons for self-medication in 324 participating students were: presence of mild illness and previous experiences. High risk practices like altering the dose, discontinuation of medication and self-medication without adult guidance were observed. The likelihood of SM was 4.9 times (95%C.I.: 2.0-12.2) in students not utilizing private healthcare services than those who were utilizing these services. Increased efforts are needed to prevent the risks of self-medication in adolescents through healthcare education for both parents and adolescents.